(untitled) (Scientific journal of the Fergana State University, 2024)
To this day, there is a lot of speculation about how the a new word is made and how it is produced. This article tries to illustrate the work done in the development of ancient linguistics on the formation of words in English and Uzbek, the methods of making new words with examples in both languages. It has been explained that in the modern age of linguistics, word formation has emerged as a separate section in both languages. The article, based on the scientific work of I.V.Arnold, R.Quirk, A.Zapata, Y.N.Bortnichuk, A.Gulomov, A.Khodjiev, Sh. Rahmatullaev on the method of word formation in both languages.